Prologues to Shakespeare's Theatre : Performance and Liminality in Early Modern Drama. - Weimann, Robert (Routledge, 2004)
This remarkable study shows how prologues ushered audience and actors through a rite of passage and how they can be seen to offer rich insight into what the early modern theatre was thought capable of achieving.